2019
DOI: 10.2217/3dp-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Use of GelMA for 3D printing of Cardiac Myocytes and Fibroblasts

Abstract: Aim-To 3D print heart tissue, one must understand how the main two types of cardiac cells are affected by the printing process. Materials & methods-Effects of gelatin methacryloyl (GelMA) concentration, extruder pressure and duration of UV exposure on survival of cardiac myocytes and fibroblasts were examined using lactate dehydrogenase and LIVE/DEAD assays, bioluminescence imaging and morphological assessment. Results & conclusion-Cell survival within 3D printed cardiomyocyte-laden GelMA constructs was more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…One of the reasons behind this elastic behavior of the SPG7.5 fabricated constructs could be the due to the presence of β nanocrystals formed due to the enzymatic crosslinking of the n‐SF component of the biomaterial ink. The presence of poly‐alanine stretches in the secondary structure of the n‐SF resulted in the formation of interspersed amorphous regions within the crosslinked β‐sheet structures leading to an enhanced elastic nature . Furthermore, to understand the elastic behavior of the constructs in a dynamic condition similar to native cardiac tissue, constructs fabricated using SPG7.5, G5, and G7.5 inks were subjected to cyclic 5% strain for 40 cycles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons behind this elastic behavior of the SPG7.5 fabricated constructs could be the due to the presence of β nanocrystals formed due to the enzymatic crosslinking of the n‐SF component of the biomaterial ink. The presence of poly‐alanine stretches in the secondary structure of the n‐SF resulted in the formation of interspersed amorphous regions within the crosslinked β‐sheet structures leading to an enhanced elastic nature . Furthermore, to understand the elastic behavior of the constructs in a dynamic condition similar to native cardiac tissue, constructs fabricated using SPG7.5, G5, and G7.5 inks were subjected to cyclic 5% strain for 40 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, 3D printing techniques have facilitated a large number of naturally derived polymers to be used alone or in combination as inks, enabling the printing of complex cardiac tissue constructs. Many of these natural polymers such as gelatin, collagen, alginate, gelatin methacryloyl (GelMA),7a,b,8 and fibrin act as extracellular matrix (ECM) mimics which help to support the growth and function of the desired cells . For instance, cardiomyocyte laden hydrogels bioprinted using fibrin based bioink on a sacrificial poly‐caprolactone (PCL) support, by Wang et al, showed dense and highly aligned cardiac tissues with synchronous contraction behaviors .…”
Section: Introductionmentioning
confidence: 99%
“… Adding extra molecules, using two-cell bio-ink, and lowering the concentration of GelMA might improve cell survival and network formation. [ 89 ] Alginate & PEG-Fibrinogen (PF) Mice iPS-CM & HUVEC None The scaffold and cells are printed one after another, and then the organizations were evaluated both in vitro and in vivo . The transplanted engineered tissue can merge well with the host's heart by vasculature.…”
Section: Frontier Of 3d Bioprinting In Cardiac Tissue Engineeringmentioning
confidence: 99%
“…Regardless of the differences between each research goal, it seems that in the selection of printing materials, the use of a natural hydrogel as the main bioink backbone for encapsulating CTE cells seems to be more popular. For example, biocompatible methacrylic anhydride gelatine (GelMA) prepared by the reaction of methacrylic anhydride (MA) and gelatine [ 83 ] has recently been adopted for the production of functional CTE prints; and the reason is that the appropriate proportion of GelMA, whether in monomer form [ [84] , [85] , [86] ] or in composite form [ [88] , [89] , [90] ], addresses the basic mechanical requirements. In addition, the hydrogel assembled with a nano-improved biomaterial also shows important abilities in adapting to a 3D bioprinting heart system, which can enhance the interaction between cells and materials to form a stable structure [ 67 , 91 ].…”
Section: Frontier Of 3d Bioprinting In Cardiac Tissue Engineeringmentioning
confidence: 99%
“…Further, printer type and bioprinting approach must also be considered when choosing the appropriate bioink. Although somatic cells such as chondrocytes, fibroblasts, and cardiac myocytes have been used in 3D bioprinting, most applications rely on the inclusion of stem cells to facilitate de novo tissue development ( 12 14 ). Bioprinting exploits the ability of these cells to undergo self-renewal and directed differentiation to control tissue development and ultimately generate bioprinted tissues.…”
Section: Cellular Component Of Bioinkmentioning
confidence: 99%